2007
DOI: 10.1002/humu.20601
|View full text |Cite
|
Sign up to set email alerts
|

Germline and somaticNF1 gene mutation spectrum in NF1-associated malignant peripheral nerve sheath tumors (MPNSTs)

Abstract: About 10% of neurofibromatosis type 1 (NF1) patients develop malignant peripheral nerve sheath tumors (MPNSTs) and represent considerable patient morbidity and mortality. Elucidation of the genetic mechanisms by which inherited and acquired NF1 disease gene variants lead to MPNST development is important. A study was undertaken to identify the constitutional and somatic NF1 mutations in 34 MPNSTs from 27 NF1 patients. The NF1 germline mutations identified in 22 lymphocytes DNA from these patients included seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 57 publications
6
97
1
2
Order By: Relevance
“…17,18 Indeed, three of the somatic NF1 mutations characterised here (p.R816X, p.R304X, p.L1569X) have previously been identified as somatic lesions (two of these three mutations are CpG located and therefore compatible with a mechanism of methylation-mediated deamination of 5-methylcytosine) in both benign and malignant tumours. [41][42][43][44][45][46] A total of seven novel somatic NF1 missense mutations were identified during the course of this study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…17,18 Indeed, three of the somatic NF1 mutations characterised here (p.R816X, p.R304X, p.L1569X) have previously been identified as somatic lesions (two of these three mutations are CpG located and therefore compatible with a mechanism of methylation-mediated deamination of 5-methylcytosine) in both benign and malignant tumours. [41][42][43][44][45][46] A total of seven novel somatic NF1 missense mutations were identified during the course of this study.…”
Section: Discussionmentioning
confidence: 70%
“…47 In our study, MLPA analysis succeeded in identifying only a single intragenic deletion in one neurofibroma, indicating that mitotic recombination was the likely mechanism for LOH in the remaining 24 neurofibromas. Our previous studies found significantly higher levels (approximately 70 and 90%, respectively) of NF1-associated LOH in both PNFs and MPNSTs, 17,18 an indication that NF1-LOH may be less prominent in benign neurofibromas than in PNFs and malignant tumours. One potential confounding factor here is cellular heterogeneity, but we do not consider that this would have substantially hampered the detection of intragenic deletions and duplications by MLPA in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This observation is in accordance with previous data showing a B90% identification rate of the two NF1 hits in MPNSTs. 37 One-third (8/28) of the NF1 hits were Figure 1 Mutation dilution sequencing using NGS and Sanger methods. NGS allowed the mutation detection in all dilutions and also presented a quantitative aspect, providing the number of mutated reads.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of such rearrangements in MPNST contrast with the 5-10% found in constitutional DNAs from NF1 patients and is in accordance with previously identified MPNST somatic NF1 mutation spectrum. 37 As molecular analysis of the NF1 gene is challenging, NF1 tumour mutation-spectrum may have been less studied than other genes with gain-of-function mutations. However, NF1 was recently identified as one of the most significantly somatic mutated genes in the Cancer Genome Atlas (TCGA) that provided molecular tumour maps using exome sequencing in more than 3000 tumours from 12 cancer types.…”
Section: Discussionmentioning
confidence: 99%